2021
DOI: 10.3146/ps20-14.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Imidacloprid and Acephate for Tobacco Thrips (Thysonaptera: Thripidae) Management on Flumioxazin Injured Peanut

Abstract: Experiments were conducted in 2016 and 2017 in Stoneville, MS and Starkville, MS to determine the impact of different insecticide management options for thrips on herbicide injured peanut. Insecticide treatments included imidacloprid in-furrow at-planting, one or two foliar applications of acephate, and an untreated control with and without an application of flumioxazin. In Stoneville, herbicide applications were made immediately following planting, and in Starkville, applications were made as plants were emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Volume 50-Issue 1 ISSN: 0095-3679 2023 studies have shown that thrips can cause yield losses in peanuts where injury from a pre-or early post-emergence herbicide has occurred (Funderburk et al 1998, Drake et al 2009, Moor et al 2021). Additionally, thrips can reduce peanut yields when excessive drought slows the growth of seedlings (Funderburk et al 1998) or when saturated soils affect peanut growth (Moor et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volume 50-Issue 1 ISSN: 0095-3679 2023 studies have shown that thrips can cause yield losses in peanuts where injury from a pre-or early post-emergence herbicide has occurred (Funderburk et al 1998, Drake et al 2009, Moor et al 2021). Additionally, thrips can reduce peanut yields when excessive drought slows the growth of seedlings (Funderburk et al 1998) or when saturated soils affect peanut growth (Moor et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Volume 50-Issue 1 ISSN: 0095-3679 2023 studies have shown that thrips can cause yield losses in peanuts where injury from a pre-or early post-emergence herbicide has occurred (Funderburk et al 1998, Drake et al 2009, Moor et al 2021). Additionally, thrips can reduce peanut yields when excessive drought slows the growth of seedlings (Funderburk et al 1998) or when saturated soils affect peanut growth (Moor et al 2021). Given the complex interaction between environmental conditions, thrips populations, and seedling development, integrated pest management strategies to reduce thrips injury may vary across peanut producing geographic regions.…”
Section: Introductionmentioning
confidence: 99%